Tacrolimus for the treatment of immune-related adverse effects refractory to systemic steroids and anti-tumor necrosis factor α therapy. (July 2019) - Beardslee, Tyler; Draper, Amber; Kudchadkar, Ragini
Immunotherapy treatments in oncology have garnered much attention and use throughout the past several years. With increased use and new approvals in many different types of solid tumors and hematological malignancies, practitioners in oncology should have an appreciation and understanding of the potential adverse effects of these unique treatment approaches. The most common adverse effects with immunotherapy treatment are immune-related adverse effects with activation of patients' immune systems against a wide array of tissues and organ systems. Immune-related adverse effects are typically treated first with high doses of immunosuppressive corticosteroids. Patients with immune-related adverse effects refractory to high dose corticosteroid treatment may receive anti-tumor necrosis factor α therapy in an attempt to halt the immune system from causing further organ dysfunction. However, these agents are not always successful and other immunomodulatory agents should be considered for refractory cases. Presented here are three patient cases supporting the use of the calcinuerin inhibitor tacrolimus to treat immune-related adverse effects refractory to corticosteroids and anti-tumor necrosis factor α.